Significance of dynamic control on suddenly expanded flow when nozzles are over, under, and perfectly expanded. (2022) - Khan, Sher Afghan; Baig, Maughal Ahmed Ali; Ridwan,; Faheem, Mohammed; Suheel, J.I; Delvi, Hamza Afser
Abstract: In this paper, investigations are carried out to quantify the usefulness of the flow control in the recirculation and the growth of the flow in the tube at supersonic Mach numbers for pipe diameter 18 mm. Only those cases are shown when there is an effect of the flow control management on the stream pattern. Mach numbers of study are 1.87, 2.2, and 2.58 at various expansion levels for duct sizes 2D, 4D, 6D, and 10D. For the highest duct lengths, 6D and 10D flow fields of the duct turn oscillatory and control reversal phenomena are observed. For short ducts 1D and 2D, no such phenomena are seen. When nozzles face under-expanded or over-expanded flow at Mach 1.87 and 2.2, the flow control management does not give the needed outcomes and results in decreased pressure. Also, it is seen that at Mach 2.58, nozzles remain over-expanded, and when control is used, they end up in a rise of pressure of the tube. The minimum duct size requirement for the first two Mach is 1D, and for the highest Mach of the study, it is 3D.